Variety of Connotation Meanings in the Novel ‘Tak Ada Embusan Angin’ by Aveus Har - Putri, Rossa Cahyani; Marzuqi, Iib; Wangi, Nisaul Barokati Seliro (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
Connotation is the meaning of a word that is not in accordance with it’s actual meaning. The novel 'Tak Ada Embusan Angin' by Aveus Har contains many words with connotations that are interesting to research. The aim of this research is to describe the various connotative meanings in the novel 'Tak Ada Embusan Angin' by Aveus Har. This research uses a qualitative descriptive research type. The data in this research are various connotative meanings in the novel 'Tak Ada Embusan Angin' by Aveus Har. The data source in this research is the novel ''Tak Ada Embusan Angin' by Aveus Har. The results of the analysis show that there are seven types of connotative meanings contained in the novel 'Tak Ada Embusan Angin' by Aveus Har, namely (1) high connotation 41 data, (2) friendly connotation 11 data, (3) dangerous connotation 6 data, (4) no connotation appropriate 5 data, (5) unpleasant connotation 10 data, (6) harsh connotation 8 data, and (7) hard connotation 44 data. The total number is 125 data.